2017
DOI: 10.3390/polym9120680
|View full text |Cite
|
Sign up to set email alerts
|

Confinement Effects on Polymer Dynamics: Thermo-Responsive Behaviours of Hydroxypropyl Cellulose Polymers in Phospholipid-Coated Droplets (Water-in-Oil Emulsion)

Abstract: Abstract:In order to construct the artificial cells and to understand the physicochemical properties of living cells, it is important to clarify the cell-sized confinement effect on the behaviours of bio-inspired polymers. We report the dynamic behaviours of aqueous hydroxypropyl cellulose (HPC) solution coated with phospholipids in oil (water-in-oil droplets, W/O droplets), accompanied by an increase in the temperature. We directly observed the beginning of phase separation of HPC solution using a fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The effects of droplet size and temperature on the dynamic behaviors of an aqueous solution of hydroxypropyl cellulose (HPC) coated with phospholipids in oil (water-in-oil droplets) were studied by Yoshida et al [157]. The beginning of phase separation of the HPC solution, one of the most representative biocompatible polymers, with its main component (multi-sugar chain) being found in living cells, was observed by the authors, who demonstrated that the start time of phase separation is decreased with the increase in droplet size [157].…”
Section: Biomembrane Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The effects of droplet size and temperature on the dynamic behaviors of an aqueous solution of hydroxypropyl cellulose (HPC) coated with phospholipids in oil (water-in-oil droplets) were studied by Yoshida et al [157]. The beginning of phase separation of the HPC solution, one of the most representative biocompatible polymers, with its main component (multi-sugar chain) being found in living cells, was observed by the authors, who demonstrated that the start time of phase separation is decreased with the increase in droplet size [157].…”
Section: Biomembrane Structurementioning
confidence: 99%
“…The effects of droplet size and temperature on the dynamic behaviors of an aqueous solution of hydroxypropyl cellulose (HPC) coated with phospholipids in oil (water-in-oil droplets) were studied by Yoshida et al [157]. The beginning of phase separation of the HPC solution, one of the most representative biocompatible polymers, with its main component (multi-sugar chain) being found in living cells, was observed by the authors, who demonstrated that the start time of phase separation is decreased with the increase in droplet size [157]. This study of cell-size confinement effects on the dynamic behaviors of biocompatible polymers highlighted the importance of droplet size and of the lower critical solution temperature for the dynamic phase behavior, not only for artificial cell construction, but also for understanding the physicochemical properties of living cells [157].…”
Section: Biomembrane Structurementioning
confidence: 99%
“…Artificial model systems of biological membranes, such as liposomes and water-in-oil (W/O) droplets, are quite beneficial for studies of the dynamic behaviors of biological membranes owing to the fact that liposomes and W/O droplets can be easily prepared and possess a simple membrane structure [4][5][6]. Using such liposomes, it was shown that the surfactants, such as Triton X-100 and ethanol, with amphiphilic properties have an ability to invade the lipid bilayers and to form lipid/surfactant mixed micelles, which consequently induce destabilization and destroy the lipid bilayer structure [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that the start time of the phase separation into HPCÀ and water-rich phases is strongly correlated with droplet size. [35] In that case, the concentration of HPC in the droplets was 40 wt%, and we focused on the droplet size dependency. Further experiments are required for a better understanding of dynamic behaviours of confined aqueous HPC solutions and the effect of lipid head groups located in droplet/oil interfaces.…”
mentioning
confidence: 99%
“…The experimental setup is the same as in our previous study. [35] Figure 2 shows typical time-dependent fluorescence microscopic images of aqueous HPC droplets without and with lipid coating. The green fluorescent dye is calcein, which dissolves in water.…”
mentioning
confidence: 99%